Proteomic analysis of human epithelial lining fluid by microfluidics‐based nanoLC‐MS/MS: A feasibility study. Issue 18 (22nd August 2013) - Franciosi, Lorenza; Govorukhina, Natalia; Fusetti, Fabrizia; Poolman, Bert; Lodewijk, Monique E.; Timens, Wim; Postma, Dirkje; ten Hacken, Nick; Bischoff, Rainer; Kašička, Václav
<x xml:space="preserve">Abstract</x> Microfluidics‐based nanoLC‐MS/MS (chipLC‐MS/MS) was used to identify and quantify proteins in epithelial lining fluid (ELF), collected during bronchoscopy from the main bronchi of chronic obstructive pulmonary disease (COPD) patients and healthy controls using microprobes. ELF is a biofluid that is well suited to study pathophysiological processes in the lung, because it contains high concentrations of biologically active molecules. 1D‐PAGE followed by in‐gel tryptic digestion and chipLC‐MS/MS resulted in identification of approximately 300 proteins. A comparative study of ELF from COPD patients and non‐COPD controls using chemical stable isotope labeling (iTRAQ®‐8Plex) showed that the levels of lactotransferrin, high‐mobility group protein B1 (HMGB 1), alpha 1‐antichymotrypsin and cofilin‐1 differed significantly in ELF from COPD patients and non‐COPD controls (p‐values < 0.05). These results were reproduced in another, independent set of ELF samples from COPD patients and non‐COPD controls and further validated by immunohistochemistry. This study shows the feasibility of performing chipLC‐MS/MS and quantitative proteomics in human ELF.